2009
DOI: 10.1016/j.jmp.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A new dynamical model of brainstorming: Linear, nonlinear, continuous (simultaneous) and impulsive (sequential) cases

Abstract: a b s t r a c tIn this paper, we extended the linear dynamical model of [Brown, V., Paulus, P. B. (1996). A simple dynamic model of social factors in group brainstorming. Small Group Research, 27, on two accounts. First, we modelled the sequential type brainstorming using impulsive differential equations by treating each category as an impulse and tested its validity in the two experiments that investigated and demonstrated the beneficial effects of sequential priming and memory in individual brainstorming. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
2
21
1
Order By: Relevance
“…Furthermore, providing participants 10 categories led them to generate more ideas than providing them with only two categories in the sequential task, with time al lotted the same in both conditions. Coskun and Yilmaz (2009) also found that the participants in a sequential condition generated more ideas in a brainstorming task than did the participants in the nonsequential condition. Because the partici pants were cued with categories every 5 min, the sequential participants steadily generated ideas throughout the 30 min of the brainstorming task.…”
Section: Methodsmentioning
confidence: 80%
“…Furthermore, providing participants 10 categories led them to generate more ideas than providing them with only two categories in the sequential task, with time al lotted the same in both conditions. Coskun and Yilmaz (2009) also found that the participants in a sequential condition generated more ideas in a brainstorming task than did the participants in the nonsequential condition. Because the partici pants were cued with categories every 5 min, the sequential participants steadily generated ideas throughout the 30 min of the brainstorming task.…”
Section: Methodsmentioning
confidence: 80%
“…In their experimentations in [9], Coskun and Yilmaz noted that in the first half of the brainstorming session, the non-cognitive model fits better to the number of ideas recorded than the cognitive model, and conversely, the cognitive model was better in the second half of the session. Therefore, the use of the both models (non-cognitive and cognitive) and our both optimization models (Euler based and RungeKutta based) could be interesting for the prediction of ideas number.…”
Section: Discussionmentioning
confidence: 99%
“…The matching is estimated by the distance between productions of an individual and the average of others' productions. Following Coskun and Yilmaz [9], we add the constraint ‫‬ ሺ‫ݐ‬ሻ Ͳ to model the fact that ideas rate is always positive or null. A possible effect of this constraint is to break the linearity of the differential equations.…”
Section: Non-cognitive Model Of Brainstormingmentioning
confidence: 99%
See 2 more Smart Citations